The Prevalence and Molecular Spectrum of α- and β-Globin Gene Mutations in 14,332 Families of Guangdong Province, China - Yin, Aihua; Li, Bing; Luo, Mingyong; Xu, Longchang; Wu, Li; Zhang, Liang; Ma, Yuanzhu; Chen, Tingting; Gao, Shuang; Liang, Juqing; Guo, Hao; Qin, Danqing; et al. (PloS one, 2014)
To reveal the familial prevalence and molecular variation of α- and β-globin gene mutations in Guangdong Province. A total of 40,808 blood samples from 14,332 families were obtained and analyzed for both hematological and molecular parameters. A high prevalence of α- and β-globin gene mutations was found. Overall, 17.70% of pregnant women, 15.94% of their husbands, 16.03% of neonates, and 16.83% of couples (pregnant women and their husbands) were heterozygous carriers of α- or β-thalassemia. The regions with the highest prevalence were the mountainous and western regions, followed by the Pearl River Delta; the region with the lowest prevalence was Chaoshan. The total familial carrier rate (both spouses were α- or β-thalassemia carriers) was 1.87%, and the individual carrier rates of α- and β-thalassemia were 1.68% and 0.20%, respectively. The total rate of moderate-to-severe fetal thalassemia was 12.78% among couples in which both parents were carriers. There was a high prevalence of α- and β-thalassemia in Guangdong Province. This study will contribute to the development of thalassemia prevention and control strategies in Guangdong Province.